Komunikasi Pemasaran Teras Bocimi Kafe Dalam Meningkatkan Jumlah Konsumen Di Masa Pandemi - Nur Aini Parwitasari (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
Integrated Marketing Communications (IMC) is a concept in which a company integrates and coordinates various marketing communication channels to send clear, consistent, and attractive messages about the company and its products. Marketing communication to consumers by the management of Teras Bocimi Café will be more measurable and planned. This research uses qualitative and descriptive methods. The qualitative research approach uses 6 dimensions to implement marketing communication in Teras Bocimi Café, namely direct marketing, promotion, public relations and publicity, personal selling, word-of-mouth marketing, and events and experiences initiated by Kolter and Keller to implement communication. Based on field data, not all dimensions run well, some do not run and are not implemented at Teras Bocimi Cafe.